Enhancing gas production from Class II hydrate deposits through depressurization combined with low-frequency electric heating under dual horizontal wells. (15th October 2021) - Zhao, Ermeng; Hou, Jian; Ji, Yunkai; Liu, Yongge; Bai, Yajie
Abstract: Class II hydrate deposits are characterized by a mobile water zone (WZ) underneath the hydrate-bearing layer (HBL) and are encountered in permafrost and deep-sea sediments. In this work, an efficient method of depressurization combining low-frequency electric heating under dual horizontal wells is proposed to exploit Class II hydrate deposits, in which two parallel horizontal wells are arranged in the HBL and the WZ. Based on the geological parameters in the Mallik deposit, the energy recovery behaviors are studied through a numerical simulation approach. Electric heating significantly improves hydrate dissociation and gas production compared with the depressurization method. However, gas production lags electric heating for a long time, and the energy efficiency ratio decreases with time in the later stage. To address these shortcomings, two additional electric heating schemes are designed and optimized. The results show that the additional wellbore heating at the beginning of production accelerates the dissociation of hydrates near the production well, thus greatly reducing the lag time. When electric heating is terminated after the 800th day, the cumulative gas production is reduced by 9.1%, but the energy efficiency ratio is improved as high as 48.71, which confirms the great potential of the proposed method. Highlights: The method of depressurization combining low-frequency electric heating under dual horizontal wells is proposed. Gas production behavior and heat transfer characteristics are analyzed by numerical simulation. The low-frequency electric heating significantly improve the hydrate dissociation and gas recovery. The enforced heat convection from bottom water enhances heat utilization efficiency.